1990
DOI: 10.3109/01050399009070771
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Hearing Threshold MeasurementsSupplementary Data on Bone-conduction and Speech Audiometry

Abstract: The reproducibility of bone-conduction pure-tone audiometry and speech recognition thresholds has been tested in groups of normal-hearing subjects. Each person was tested twice during the same day, and the test-retest difference was calculated. The reproducibility is presented as the standard deviation of this difference. Bone-conduction threshold measurements have a high degree of test-retest precision, whereas air-bone gaps show a large range of distribution in these normal-hearing subjects. This makes the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
2
7
2
Order By: Relevance
“…The average absolute difference in bone-conduction thresholds recorded in the natural and audiometric booth (3.4 ± 4.3 dB) was within previously reported bone-conduction test-retest differences (Laukli & Fjermedal, 1990;Margolis et al 2010;Swanepoel & Biagio, 2011). The average absolute test-retest variability for this same audiometer previously reported in a small group of 10 normal-hearing subjects was 7.1 ± 6.4 dB.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The average absolute difference in bone-conduction thresholds recorded in the natural and audiometric booth (3.4 ± 4.3 dB) was within previously reported bone-conduction test-retest differences (Laukli & Fjermedal, 1990;Margolis et al 2010;Swanepoel & Biagio, 2011). The average absolute test-retest variability for this same audiometer previously reported in a small group of 10 normal-hearing subjects was 7.1 ± 6.4 dB.…”
Section: Discussionsupporting
confidence: 63%
“…The average absolute test-retest variability for this same audiometer previously reported in a small group of 10 normal-hearing subjects was 7.1 ± 6.4 dB. Laukli and Fjermedal (1990) reported bone-conduction test-retest standard deviation variability between 3.2 and 4.8 dB across 250 to 4000 Hz in a small sample of normal-hearing adults. Similarly, Margolis et al (2010) reported an average absolute test-retest difference for bone-conduction thresholds of 4.1 ± 3.8 dB across frequencies.…”
Section: Discussionmentioning
confidence: 92%
“…However, in general the variation is not significantly different to reports by others. Only at 250Hz is the variation significantly greater than that reported by Laukli (Laukli & Fjermedal, 1990). In two cases the variation is significantly less than that reported by Swanepoel (2011) for manual operation of the KUDUWave audiometer at 2000Hz and overall.…”
Section: Test-retest Reliabilitycontrasting
confidence: 42%
“…To calculate the difference, the manual threshold was subtracted from the AMTAS threshold (Margolis et al, 2007). For the test-retest analysis, to conform to the method of analysis used by other studies, only data from two tests were included in the analysis rather than all three (Frank & Ragland, 1987;Laukli & Fjermedal, 1990;Margolis, Glasberg et al, 2010;Swanepoel, Mngemane et al, 2010;Swanepoel & Biagio, 2011). The results from the second and third set of thresholds were used, thereby minimising the possible learning effect resulting from the first session of automated audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…Because the thresholds with stimulation at the 4 different positions are done in consecutive order, the uncertainty can be viewed as a test-retest with the transducer disconnected between measurements. Test-retest data were not obtained in the current sample, but in a previous investigation using a masking procedure, the standard deviation for BC threshold test-retest were between 3.2 and 4.8 dB in the frequency range of 0.25 to 4 kHz (21). In that study, the 2 test situations were during the same day and not consecutive as here, and the masking sound was used while the subjects here were unilaterally deaf and did not need masking.…”
Section: Comparison With Previous Datamentioning
confidence: 79%